Sustainable Synthesis of New Antioxidants from Hydroxytyrosol by Direct Biocatalytic Esterification in Ionic Liquids - Susana Nieto; Inmaculada Lozano; Francisco J. Ruiz; Jose F. Costa; Rocio Villa; Pedro Lozano (Molecules)
Hydroxytyrosol (HT) is a nutraceutical compound, mainly found in the fruit, leaves and waste from the olive oil industry, known for exhibiting one of the highest antioxidant activities among molecules of natural origin. To harness this bioactivity in cosmetics, pharmaceuticals and the food industry, it is essential to modify the hydrophilicity of HT to enhance its compatibility with lipid-based mixtures. This chemical modification must be carried out with high selectivity to avoid compromising its radical scavenging activity. This work presents a highly efficient and selective approach to perform the biocatalytic esterification of free fatty acids (FFAs) of different alkyl chain lengths with HT in a reaction medium based on the SLIL [C12mim][NTf2]. By using a 1:2 (mol/mol) HT:FFA mixture of substrates, the HT-monoester derivative was obtained up to 77% yield after 2 h at 80 °C. The optimized molar ratio of substrates, combined with the ability to recover the SLIL for further reuse, significantly reduces waste accumulation compared to other reported strategies and results in a more sustainable approach as demonstrated by different green metrics. The antioxidant activity of HT-monoester products was fully maintained with respect to that presented by the natural HT, being stable for at least 3 months at 4 °C, as demonstrated by the DPPH and FRAP antioxidant analysis.